Dialogue Summary: Coordinating the Use of Genetic Tests and Related Services in British Columbia - Gauvin, François-Pierre; Lavis, JN (My University, 2012)
A summary of what was learned from a stakeholder dialogue that addressed problems related to coordinating the use of genetic tests, options for addressing these problems, key implementation considerations, and next steps for expanding the uptake of coordinating the use of genetic tests and related services in British Columbia.
Keywords: genetic tests; British Columbia